Uji Infektivitas Tobacco Mosaic Virus (TMV) dan Cucumber Mosaic Virus (CMV) pada Chaenopodium amaranticolor - Siti Shofiya Nasution; Raichan Izzati; Durrah Hayati (Jurnal Media Pertanian, 2023)
The infectivity test is one of the completeness in knowing the physical properties of the virus. Determination of the physical properties of the virus can be done by: Thermal inactivation point (TIP), in vitro resistance (Longevity in vitro / LIV), and dilution end point (DEP). The purpose of this study was to determine the infectivity of TMV and CMV in sap through LIV, DEP, and TIP.LIV testing is done by sap incubation until the test time (0 hours, 6 hours, and 24 hours), DEP test is done by diluting sap (not diluted, 10-1, 10-2, 10-3, 10-4, 10-5, 10-6, 10-7), while TIP test is done by heating sap at room temperature, 50oC, 70oC, 90oC for 10 minutes. The results of this study show TMV is stable compared to CMV.TMV is still infectious in sap storage for 24 hours, while CMV is not infectious between 6-24 hours after incubation. The cutoff point of sap TMV dilution is between 10-5 and 10-6, while CMV has been unable to cause symptoms in indicator plants at dilutions between 10-1 and 10-2. TMV is still infectious at 90oC temperature treatment, while CMV inactivation hot spots are 40oC and 50oC.